KUALITAS SPERMATOZOA TIKUS PUTIH (Rattus novergicus) SETELAH DIBERI DEKOK DAUN JAMBU BIJI MERAH (Psidium guajava L.) SEBAGAI SUMBER BELAJAR - Latifa, Roimil (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract -The participation ofmeninfamily planningis oftendifficult to understand, andmeansmoreplanning clinicservicesaimed atwomen, while according tothe history ofcoitus interruptusmethodinvolvingthe fullparticipation ofmenisthe oldestmethod offamily planning. The role ofmeninfamily planningis veryimportantbecausethe husbandis usuallymoredominantinpolicy makerskeluarga.Daunguava containsactive substancessuch asalkaloids, flavonoids, tannins, essential oils, avikullarin, acidandbeta-sitosterololeanolikthat areantifertilitas.Alkaloids can affect the secretion of reproductive hormones necessary for the process of spermatogenesis, essential oils work on the process of spermatogenesis but not in sperm transport, tannins can agglomerate resulting in lower sperm motility and viability of sperm (Wien.W. & Dian S. 1997).The purpose of this study was to identify a range of doses dekok red guava leaves on rat sperm quality.The kind of this research is true research.Parameter experiments used were morphology (abnormality) and mortality of spermatozoa. The population in this study is a white male rats. The samples used were 12 heads, divided into 4 treatments each consisting of 3 replicates, using completely randomized design (CRD) , a data analysis technique with one factor ANOVA and LSD continued 1 %.The results showed no significant effect of several doses dekok red guava leaves against a white rat sperm quality. Effective doses decrease sperm quality is 7 g/hr. The result of research can be used as learning resource for students of biology for animal reproduction course.Â Keywords: spermatozoa quality, red guava leaves, white male rats